Boundary layer features observed during NAME 2004 - Stuckmeyer, Elizabeth Anne, author; Rutledge, Steven A., advisor; Johnson, Richard H., committee member; Weckwerth, Tammy M., 1966-, committee member; Ramírez, Jorge A., committee member (Colorado State University. Libraries, 2011)
S-Pol radar data from the North American Monsoon Experiment (NAME) are examined to investigate the characteristics of sea breezes that occurred during the North American Monsoon in the late summer of 2004, as well as their role in modulating monsoon convection. Zero degree plan position indicated (PPI) scans were examined to determine the presence of a sea breeze fine line in the S-Pol radar data. Sea breeze fine lines were typically observed over land very near the coast of the Gulf of California (GoC), and usually moved onshore around 1700-1800 UTC (11:00 AM - 12:00 PM local time), and then continued to move slowly inland on the coastal plain. The sea breezes typically moved on land and dissipated before any significant interactions with Sierra Madre Occidental (SMO) convection could occur. Fine lines varied in reflectivity strength, but were typically around 10 to 20 dBZ. Surface winds from the Estación Obispo (ETO) supersite were analyzed to confirm the presence of a shift in wind direction on days in which a fine line had been identified. Typically winds changed from light and variable to consistently out of the west or southwest. Vertical plots of S-Pol reflectivity were created to examine sea breeze structure in the vertical, but these were not found to be useful as the sea breeze signature was nearly impossible to distinguish from other boundary layer features. Horizontal structure was further investigated using wind profiler relative reflectivity, vertical velocity, and horizontal winds from the profiler located at ETO. Relative reflectivity and vertical velocity fields revealed a complex boundary layer structure on some days of repeating updrafts and downdrafts. Further examination of S-Pol PPI data revealed that these vertical motions are likely due to the presence of horizontal convective rolls. Profiler horizontal winds revealed that the depth and vertical structure of the sea breezes varied significantly from day to day, but that the height of the sea breeze is around 1 km above the ground. Sea breezes observed during NAME almost never initiated convection on their own. It is hypothesized that a weak thermal contrast between the GoC and the land leads to comparatively weak sea breezes, which don't have enough lift to trigger convection.
Keywords: boundary layer; sea breeze; radar; NAME